Rodent preference for acorns - Arco Montero, José María del (2023)
The relationship between scatter-hoarding rodents and oak species has been considered on a scale from antagonism to mutualism. Depending on the costs and benefits, the outcome of the relationship can be found at one extreme or the other. Costs have included destruction of acorns that occurs during predation, but not all acorns attacked lose their embryos. As representatives of the mutualistic end, we present two species with this behavior (Mus spretus and Apodemus sylvaticus). Representing the antagonistic extreme, we present a predatory species that destroys the embryo (Microtus arvalis). The objective of this study is to test the preferences of both rodent groups for acorns. The results showed that there is one acorn species (Quercus ilex) that is preferred by the three rodent species. This acorn species has high concentrations of nutrients, low concentrations of tannins and thin shell. These characteristics attract the attention of rodents that could carry these acorns. There are two other acorn species (Quercus suber and Quercus rubra) that are consumed with little intensity for having low concentrations of nutrients, high concentration of tannins and thick shell. These characteristics escaping predators although transportation is not guaranteed. These acorns would germinate and emerge under the trees that have produced them and increase intraspecific competition. Coincidence preferences shown by the three rodent species poses a risk for the oak species, since the recent arrival of the predator (antagonist) species in the study area could paralyze the dispersal process carried out by the other two mutualistic species through predation. Departamento de Ciencias Agroforestales